THE CORRELATION BETWEEN STUDENTS’ SELF-EFFICACY AND ENGLISH SPEAKING SKILLS AT EIGHT GRADE OF JUNIOR HIGH SCHOOL 09 BENGKULU TENGAH - Reko Serasi; Istia Fransiska (English Education Study Program Faculty of Teacher Training and Education, 2020)
The aims of this research are to know the correlation between students’ self-efficacy and their speaking skill at first semester at eight grade junior high school 09 Bengkulu Tengah. In this research used a correlation research to find out the relationships between two or more variables studied without any attempt to influence them. This study has two variables, variable (X) is students Self-Efficacy and variable (Y) is speaking skill. The researcher was carried out at SMPN 09 Bengkulu Tengah. The population was first semester at eight grade of junior high school 09 Bengkulu Tengah, there were 128 students. Out of this population, 30 students were taken as sample. The sampling technique used is simple random sampling. The researcher used questionnaire to obtain the data of Self-Efficacy categories and speaking test to obtain data their speaking skill. To test correlation, the researcher uses two ways: calculating manually by using Pearson’s Correlation Prosuct Moment formula and by using SPSS program. From the calculation, the correlation coefficient is 0,864 (the value of rcount). The critical values of rtable on the significant level of 5% with N=30, and rtable = 0,361. It means that rcount was higher than rtable (0,864 > 0,361). The hypothesis accepted in this research was the alternative (H1), while the null hypothesis (H0) was rejected. The finding showed that there is a positive correlation between Students Self-efficacy and speaking skill.